HIV-1 is Transported into the Central Nervous System by Trafficking Infected Cells - Laura Kincer; Gretja Schnell; Ronald Swanstrom; Melissa Miller; Serena Spudich; Joseph Eron; Richard Price; Sarah Joseph (Case Western Reserve University, 2023)
Background: In this work, we carried out a cross-sectional study examining HIV-1 and HCV free virus concentrations in blood and cerebrospinal fluid (CSF) to determine whether HIV-1 enters the central nervous system (CNS) passively as virus particles or in the context of migrating infected cells. If virions migrate freely across the blood-cerebrospinal fluid barrier (BCSFB) or the blood-brain barrier (BBB) then HCV and HIV-1 would be detectable in the CSF at proportions similar to that in the blood. Alternatively, virus entry as an infected cell would favor selective entry of HIV-1. Methods: We measured HIV-1 and HCV viral loads in the CSF and blood plasma of 4 co-infected participants who were not on antiviral regimens for either infection. We also generated HIV-1 env sequences and performed phylogenetic analyses to determine whether HIV-1 populations in the CSF of these participants were being maintained by local replication. Results: While CSF samples taken from all participants had detectable levels of HIV-1, HCV was not detectable in any of the CSF samples despite participants having HCV concentrations in their blood plasma, which exceeded that of HIV-1. Further, there was no evidence of compartmentalized HIV-1 replication in the CNS (Supplementary Figure 1). These results are consistent with a model where HIV-1 particles cross the BBB or the BCSFB within infected cells. In this scenario, we would expect HIV-1 to reach the CSF more readily because the blood contains a much greater number of HIV-infected cells than HCV-infected cells. Conclusions: HCV entry into the CSF is restricted, indicating that virions do not freely migrate across these barriers and supporting the concept that HIV-1 is transported across the BCSFB and/or BBB by the migration of HIV-infected cells as part of an inflammatory response or normal surveillance.